The Leadership Role of the Head of Pkbm Merah Putih in Building a Positive Work Culture - Helyna Riskawaty; Etioti Br Purba; Edi Sulistiawan; Aslamiah Aslamiah; Celia Cinantya (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze the effectiveness of the principal's leadership at PKBM Merah Putih Kotabaru in building a positive work culture and its impact on teacher performance. The objectives are to identify the role of the principal in fostering a positive work culture, the leadership styles applied, and the impact of this culture on teacher performance. A qualitative approach was used, focusing on a case study to deeply explore leadership practices at PKBM Merah Putih Kotabaru. Data were collected through in-depth interviews and observations involving the principal, teaching staff, and students, with analysis conducted using NVivo 14 software. The results indicate that the principal's inclusive leadership style, characterized by appreciation, active listening, a clear vision, and team development focus, effectively creates a positive work culture. This culture fosters a conducive and motivating work environment. Respondents highlighted the importance of clear communication, open discussions, and continuous development efforts by the principal. The study concludes that effective leadership significantly contributes to building a positive work environment, enhancing teacher performance, and improving the overall quality of education at PKBM Merah Putih Kotabaru.